Servant Leadership: Educational Institution - Rahayani, Yayan (English Education Department, Universitas Islam Indonesia, 2010)
Servant leadership was firstly introduced by Robert K. Greenleaf in his essay The servant as leader in 1970. Green leaf had spent his life working for a telecommunication company before he eventually dedicated his life as a public teacher. He concerned about wider society and global culture. His belief is that authentic change happened only when it began in the inner solitude of single individuals. Greenleaf explains that the servant leader is servant first with the natural feeling that one wants to serve. The leader-first and the servant-first are two extreme types of leaders with the servant-first leader taking care to make sure other people's highest priority needs are being served. Following the desire to serve may be a conscious choice that brings one to aspire to lead. In educational setting, servant leadership seems to be the most compatible leadership compare to transformational and charismatic leadership. Teachers serve the need of student and in turn this will encourage students consciously to become leader for themselves to be more independent.